2019
DOI: 10.1186/s12864-019-5646-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of Bacillus paralicheniformis MDJK30 with its closely related species reveals an evolutionary relationship between B. paralicheniformis and B. licheniformis

Abstract: Background Members of the genus Bacillus are important plant growth-promoting rhizobacteria that serve as biocontrol agents. Bacillus paralicheniformis MDJK30 is a PGPR isolated from the peony rhizosphere and can suppress plant-pathogenic bacteria and fungi. To further uncover the genetic mechanism of the plant growth-promoting traits of MDJK30 and its closely related strains, we used comparative genomics to provide insights into the genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 66 publications
2
40
0
Order By: Relevance
“…In the comparative genomic era, numerous adjustments have been done in the last years to clarify the phylogeny of the B. subtilis complex, which includes, among others, species, such as B. velezensis, B. amyloliquefaciens, B. atrophaeus, B. subtilis subspecies subtilis, B. licheniformis, B. pumilus, and B. siamensis with potential as biocontrol agents (Expósito et al, 2017;Fira et al, 2018;Maksimov et al, 2020), and which led to some confusion in species names but also to misassignments (Dunlap et al, 2016;Fan et al, 2017;Harwood et al, 2018;Du, 2019;Torres Manno et al, 2019). Many isolates, such as strains FZB42, QST713, or SQR9 formerly assigned to the B. subtilis or B. amyloliquefaciens species have been reclassified as B. velezensis representing the model species for plant-associated bacilli (Dunlap et al, 2016;Fan et al, 2017).…”
Section: Diversity and Bioactivities Of Bacillus Bsmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the comparative genomic era, numerous adjustments have been done in the last years to clarify the phylogeny of the B. subtilis complex, which includes, among others, species, such as B. velezensis, B. amyloliquefaciens, B. atrophaeus, B. subtilis subspecies subtilis, B. licheniformis, B. pumilus, and B. siamensis with potential as biocontrol agents (Expósito et al, 2017;Fira et al, 2018;Maksimov et al, 2020), and which led to some confusion in species names but also to misassignments (Dunlap et al, 2016;Fan et al, 2017;Harwood et al, 2018;Du, 2019;Torres Manno et al, 2019). Many isolates, such as strains FZB42, QST713, or SQR9 formerly assigned to the B. subtilis or B. amyloliquefaciens species have been reclassified as B. velezensis representing the model species for plant-associated bacilli (Dunlap et al, 2016;Fan et al, 2017).…”
Section: Diversity and Bioactivities Of Bacillus Bsmsmentioning
confidence: 99%
“…The siderophore bacillibactin is highly conserved in the B. subtilis group (Figure 1) FIGURE 1 | Main non-ribosomal BSMs produced by the various species in the B. subtilis complex. The BSMs production is indicated for the following species B. subtilis, B. siamensis, B. velezensis, B. atrophaeus, B. amyloliquefaciens, B. pumilus, and B. licheniformis by a green square whereas red square indicates an absence of production of the BSMs in this species (Zhao and Kuipers, 2016;Fan et al, 2017;Harwood et al, 2018;Du, 2019;Torres Manno et al, 2019). The surfactins, iturins, and fengycins groups include lichenycin (1;AA1:L-Gln) and pumilacidin (1;AA4: L-Leu, AA7 = I-Ile); mycosubtilin (2;AA6: D-Ser, AA7 = L-Thr) and bacillomycin (2; AA6: D-Ser, AA7 = L-Asn); maltacin (4;AA1: L-Ser), agrastatin (4;AA10: L-Val) and plipastatin (4;AA9: D-Tyr), respectively.…”
Section: Diversity and Bioactivities Of Bacillus Bsmsmentioning
confidence: 99%
“…Analysis of Antagonistic Activities (Du et al, 2019) The pathogenic hyphae were taken as a rondure of 6-mm diameter and then placed on the center of a potato dextrose agar (PDA) plate. The plate was then incubated for 2 days at 28 • C. Strains were then streaked at a distance of 1 cm from the edge of the pathogenic fungal hyphae and cultured at 28 • C for another 2 days.…”
Section: Analysis Of Degrading Proteinmentioning
confidence: 99%
“…The identification of these isolates as Bacillus species is in agreement with the findings of previous study 9 . It was also observed previously that the accurate taxonomic assignment depends upon the region of 16S rRNA gene that it targeted during sequencing 10,11 . Phylogenetic research showed that thermophiles are abundant in many more extreme environments 12,13&14 .…”
Section: Gene Sequencesmentioning
confidence: 67%